2020
DOI: 10.5194/acp-2020-530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancement of secondary aerosol formation by reduced anthropogenic emissions during Spring Festival 2019 and enlightenment for regional PM<sub>2.5</sub> control in Beijing

Abstract: Abstract. A comprehensive field experiment measuring aerosol chemical and physical properties at a suburban site in Beijing around the 2019 Spring Festival was carried out to investigate the impact of reduced anthropogenic emissions on aerosol formation. Sharply reduced sulfur dioxide (SO2) and nitrogen dioxide (NO2) concentrations during the festival holiday resulted in an unexpected increase in the surface ozone (O3) concentration, leading to enhancement of the atmospheric oxidation capacity. Simultaneously,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The Chinese New Year (CNY) holiday has been widely used as a naturally controlled experiment to investigate the response of gaseous and particulate matter (PM) species to the changes in anthropogenic emissions ( Jiang et al, 2015 ; Wang et al, 2017 ; Wang et al, 2021 ), and also the period of coronavirus disease (COVID-19) outbreak when the cities implemented lockdown measures ( Dai et al, 2021 ; Javed et al, 2021 ; Sun et al, 2020 ). Previous studies have found ubiquitous reductions in aerosol and gaseous species from primary emissions during the CNY while secondary aerosol species showed less reductions and even increases due to enhanced secondary production.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese New Year (CNY) holiday has been widely used as a naturally controlled experiment to investigate the response of gaseous and particulate matter (PM) species to the changes in anthropogenic emissions ( Jiang et al, 2015 ; Wang et al, 2017 ; Wang et al, 2021 ), and also the period of coronavirus disease (COVID-19) outbreak when the cities implemented lockdown measures ( Dai et al, 2021 ; Javed et al, 2021 ; Sun et al, 2020 ). Previous studies have found ubiquitous reductions in aerosol and gaseous species from primary emissions during the CNY while secondary aerosol species showed less reductions and even increases due to enhanced secondary production.…”
Section: Introductionmentioning
confidence: 99%